2016
DOI: 10.1371/journal.pone.0160520
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq Analyses Identify Tumor Necrosis Factor-Mediated Inflammation as a Major Abnormality in ALS Spinal Cord

Abstract: ALS is a rapidly progressive, devastating neurodegenerative illness of adults that produces disabling weakness and spasticity arising from death of lower and upper motor neurons. No meaningful therapies exist to slow ALS progression, and molecular insights into pathogenesis and progression are sorely needed. In that context, we used high-depth, next generation RNA sequencing (RNAseq, Illumina) to define gene network abnormalities in RNA samples depleted of rRNA and isolated from cervical spinal cord sections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 98 publications
6
73
0
Order By: Relevance
“…In our prior work using gene expression as a proxy for cell activity, we reported that inflammation, and in particular that mediated by TNF-α, in our cervical spinal cord specimens appeared to be playing an etiologic role [36], but inflammation was not the only process we found to be disturbed. In the present study we isolated with laser capture micro dissection between ~600 and ~1300 anterior motor neurons per sample from the ALS and CTL cervical spinal cord sections available to us.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our prior work using gene expression as a proxy for cell activity, we reported that inflammation, and in particular that mediated by TNF-α, in our cervical spinal cord specimens appeared to be playing an etiologic role [36], but inflammation was not the only process we found to be disturbed. In the present study we isolated with laser capture micro dissection between ~600 and ~1300 anterior motor neurons per sample from the ALS and CTL cervical spinal cord sections available to us.…”
Section: Discussionmentioning
confidence: 55%
“…Minimum Phred scores were 20 (sequencing accuracy = 99%). Trimmed sequences were aligned against the human hg38 genome using Tophat2/Bowtie2 and quantitated against the hg38 transcriptome using Cufflinks (JPB) as described in [36]. Statistics utilized version 7 of Prism for Mac (www.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4.7) The AD population was slightly older (but not significantly so) at death (AD = 78 +/-3 years; CTL = 71 +/-4 years; p = 0.19 by t-test). Coding gene RNAseq was carried out as described in our earlier work [20], which provides links to all software algorithms and Unix texts used. Briefly, total RNA samples were treated to remove ribosomal RNA's (Ribo-Free, Illumina) then Illumina multiplex sequencing oligonucleotides were attached.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized a format similar to that described in our earlier work [20]. Briefly, compressed, paired-end sequencing files in FastQ format for each mRNA sample were downloaded, decompressed and examined in FastQC.…”
Section: Paired-end Mrna Librariesmentioning
confidence: 99%